The effect of the anti-inflammatory drug sodium salicylate in mature periparturient dairy cattle and immortalized bovine mammary epitheilal (MAC-T) cells - Montgomery, Shawnee (Kansas State University, 2014)
During the transition period, 3 wk before to 3 wk after calving, dairy cows experience a variety of sudden hormonal and metabolic shifts that could result in metabolic disorders or diseases, which can be detrimental to the productive life and longevity of the cow. Cows undergo a negative energy balance, where they cannot consume enough feed to meet their energy requirements. To make up this deficit, cows mobilize adipose tissue in the form of non-esterified fatty acids (NEFA) which are transported to the liver and are either used for fuel or stored as triglycerides. High levels of circulating NEFA can lead to endoplasmic reticulum (ER) stress, which is linked to inflammation. This low-grade inflammation can compromise cell function. To mitigate this inflammation, sodium salicylate, a non-steroidal anti-inflammatory drug (NSAID), was given to mature (3+ parity) cows for 7 d after parturition via their drinking water. Blood was collected daily and a glucose turnover assay was performed. Liver, muscle, and adipose tissue was collected on d 7. Overall, it appeared that SS increased insulin sensitivity and depressed gluconeogenesis post-transcriptionally. Multiple in vitro studies were performed on immortalized bovine mammary epithelium (MAC-T) cells to determine the action of SS when ER stress was induced with palmitate (PALM). Treatment with SS did not mitigate, and in some cases exacerbated, the ER stress response. The addition of bovine serum albumin (BSA), a common component of cell culture media, may alter reactive oxygen species (ROS) measurements due to its antioxidant property. Overall, SS seems to alter metabolic processes and the cellular response to stress.
Keywords: Transition cow; NSAID; Inflammation; UPR; Animal Sciences (0475)